2021
DOI: 10.1016/j.ijrobp.2020.12.062
|View full text |Cite
|
Sign up to set email alerts
|

CLTRN, Regulated by NRF1/RAN/DLD Protein Complex, Enhances Radiation Sensitivity of Hepatocellular Carcinoma Cells Through Ferroptosis Pathway

Abstract: Background Radiotherapy is a viable treatment option for patients with unresectable hepatocellular carcinoma (HCC). However, radiation resistance is an issue that needs to be addressed. In this context, cumulative evidence supports the functional roles of a variety of RNA or proteins in radioresistance, and suggests that the modulation of their expression may constitute a novel radiosensitization approach. Here, we investigated the ability of collectrin (CLTRN) to enhance the radiosensitivity in HCC patients f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Depletion of mitochondrial antioxidants including Coenzyme Q with FIN56, a known ferroptosis inducer, diminishes cancer cell survival following radiotherapy. The glycoprotein collectrin improves radiotherapy sensitivity through ferroptosis induction in the setting of hepatocellular carcinoma [54].…”
Section: Therapeutic Opportunities To Enhance Radiotherapy Efficacy Via Ferroptosis Inductionmentioning
confidence: 99%
“…Depletion of mitochondrial antioxidants including Coenzyme Q with FIN56, a known ferroptosis inducer, diminishes cancer cell survival following radiotherapy. The glycoprotein collectrin improves radiotherapy sensitivity through ferroptosis induction in the setting of hepatocellular carcinoma [54].…”
Section: Therapeutic Opportunities To Enhance Radiotherapy Efficacy Via Ferroptosis Inductionmentioning
confidence: 99%
“…The connection between IR-induced ferroptosis and antitumor immunity might be linked to many factors such as radiation dose and type. The previous studies have indicated that IR induces tumor cell ferroptosis and ferroptosis improves the radiosensitivity of tumor cells (10,63,64). Based on this, RT combined with ferroptosis inducers may improve the therapeutic effect of RT by increasing lipid peroxidation and promoting immune response rather than DNA damage or caspase activation (65).…”
Section: Immunogenic Forms Of Cell Deathmentioning
confidence: 94%
“…Radiotherapy induces ferroptosis by down-regulation of SLC7A11 and up-regulation of ACSL4, resulting in GSH production, increasing lipid synthesis, and subsequent oxidative damage ( Lang et al, 2019 ; Lei et al, 2020 ). Studies have found that collectrin (CLTRN), as a target of radiation, is regulated by NRF1 (nuclear respiratory factor 1)/RAN (RAS oncogene family)/DLD (dihydrolipoamide dehydrogenase) protein complex and enhances the radiosensitivity of HCC cells through ferroptosis ( Yuan et al, 2021 ). A combination of gene therapy and radiation therapy is one way forward, allowing the radiation doses to be reduced and the side effects to be reduced.…”
Section: Treatment Of Ferroptosis In Hccmentioning
confidence: 99%